Idiopathic granulomatous mastitis in a male breast following intravesical Bacille Calmette-Guerin treatment - Cennet Sahin; Burcin Agridag Ucpinar (Elsevier, 2020)
Idiopathic granulomatous mastitis (IGM) is a benign chronic inflammatory disorder of the breast tissue, with unknown etiology. IGM is extremely rare among male gender. In this case report, we present a male patient with superficial high grade bladder cancer, who was complaining of a palpable mass in his right breast for two weeks following intravesical Bacillus Calmette-Guerin (BCG) treatment. There was an assymetrical, mass-like density without distinct contours in retroareolar area of the right breast. US guided core-needle biopsy was performed. Histopathology confirmed the diagnosis of IGM. To our knowledge, this is the first case of IGM following intravesical BCG administration. Keywords: Biopsy, Imaging, Idiopathic granulomatous mastitis, Male breast cancer